Suksesi Kepemimpinan Arab Pra-Islam dan Periode al-Khulafā' al-Rashidin - Biyanto Biyanto (Islamica: Jurnal Studi Keislaman, 2006)
This article analyses the character and nature of succession in the Pre-Islamic Arabic society and in the period of al-Khulafā al-Rashidūn. It assumes that both periods share a lot in common in terms of conditions of leadership, which include seniority, bravery, generosity, good and noble family background, and the ability to safeguard the tribe. The principle of consultation (mushāwarah), which Islam talks about on many occasions, is also present in the two periods. This is despite the fact that during the period of al-Khulafā al-Rashidūn there were such practices as direct election in the case of Abi Bakr and Al b. Abi Talib-, appointment by the former caliph ?in the case of Umar b. Khattib- and election by a committee appointed by the caliph in the case of Uthmān b. Affin.